Overweight is the main behavioral risk factor associated with colorectal cancer mortality in the Brazilian population: an ecological analysis - Jonas Eduardo Monteiro dos Santos; Marina Campos Araújo; Cosme Marcelo Furtado Passos da Silva (Scientific Reports)
Abstract Colorectal cancer in Brazil is among the main public health concern. The burden of disease can be related to unhealthy lifestyle behavior and inequality in access to health services. The aim of this study was to identify the main factors associated with colorectal cancer mortality in Brazil. This is an ecological study that had the Brazilian Federal Units as the primary units of analysis. Colorectal cancer mortality data (ICD C18-C21) were obtained from Brazilian national mortality system to the year 2020. Prevalence of overweight, food consumption (fiber, whole grains and red meat), physical inactivity, smoke, alcohol consumption, the median of household income, years of study, rates of cancer treatment units and oncologist by Brazilian Federal Units were considered as factor associated to the colorectal cancer mortality. Quasipoisson Generalized Linear Models were used to associate CRC mortality and variables related to dietary intake, risk behavior, and access to health services. In 2020, there were 21,501 deaths by colorectal cancer (51% among women). Prevalence of overweight (men: IRR 1.03; CI: 1.01–1.04; women IRR 1.05; CI 1.02–1.08) and the density of oncologist (men: IRR 1.02; CI: 1.01–1.03; women IRR 1.02; CI 1.01–1.03) were the main factors associated with colorectal cancer mortality. Sociodemographic and food consumption characteristics were not statistically associated with CRC. Prevalence of overweight was the strongest factor associated with mortality from colorectal cancer in Brazil in 2020. Therefore, current public policies to reduce overweight and obesity should be prioritized and strengthened in Brazil.